The evolution of substrate discrimination in macrolide antibiotic resistance enzymes - Andrew C. Pawlowski (Nature Portfolio, 2018)
New antibiotics with reduced potential for resistance are urgently needed. Here, the authors use a multidisciplinary approach to characterize substrate discrimination in macrolide resistance kinases and present a strategy for the prediction of mutations that expand the substrate range of antibiotic-inactivating enzymes.